Torquetenovirus in pregnancy: Correlation with vaginal microbiome, metabolome and pro-inflammatory cytokines - Morselli, Sara; Foschi, Claudio; Laghi, Luca; Zagonari, Sara; Patuelli, Giulia; Camboni, Tania; Ceccarani, Camilla; Consolandi, Clarissa; Djusse, Marielle Ezekielle; Pedna, Maria Federica; Marangoni, Antonella; Severgnini, Marco; et al. (Frontiers in Microbiology, 2022)
Torquetenovirus (TTV) is a negative sense, single-stranded DNA virus present in many body fluids of apparently healthy individuals. At present, it is considered a non-pathogenic endogenous virus. TTV can be detected in the vagina of pregnant women, its abundance being modulated with the extent of immune system activation. Until now, there is only scarce information regarding the association between TTV and the composition of the vaginal environment. Therefore, this study aimed to assess the presence of TTV in the vaginal ecosystem of a cohort of white women with a normal pregnancy (n=60) at different gestational stages (first, second and third trimester) and in 9 subjects suffering a first trimester miscarriage. For each woman, we determined (i) the presence and titer of TTV, (ii) the vaginal bacterial composition by means of Nugent score and 16S rRNA gene sequencing, (iii) the vaginal metabolic profiles through 1H-NMR spectroscopy, and (iv) the vaginal concentration of two pro-inflammatory cytokines (IL-6 and IL-8). More than one third of women were found negative for TTV at all gestational stages. Although not statistically significant, the positivity for TTV dropped from 53.3% in the first to 36.6% in the third trimester. TTV loads varied greatly among vaginal samples, ranging between 2 × 101 to 2 × 105 copies/reaction. No difference in TTV prevalence and loads was observed between women with normal pregnancies and miscarriages. The presence of TTV was more common in women with a higher vaginal leucocyte count (p=0.02). The levels of IL-6 (p=0.02), IL-8 (p=0.03), propionate (p=0.001) and cadaverine (p=0.006) were significantly higher in TTV-positive samples. TTV titer was positively correlated with the concentrations of 4-hydroxyphenyllactate (p<0.0001), isoleucine (p=0.01) and phenylalanine (p=0.04). TTV-positive samples were characterized by a higher relative abundance of Sneathia (p=0.04) and Shuttleworthia (p=0.0009) In addition, a trend towards a decrease of Lactobacillus crispatus and Lactobacillus jensenii, and an increase of Lactobacillus iners was observed for TTV-positive samples. In conclusion, we found that TTV is quite common in women with normal pregnancy outcomes, representing a possible predictor of local immune status.